Radical enfranchisement in the jury room and public life - Chakravarti, Sonali (Chicago : The University of Chicago Press, 2020)
Juries have been at the centre of some of the most emotionally charged moments of political life. At the same time, their capacity for legitimate decision making has been under scrutiny, because of events like the acquittal of George Zimmerman by a Florida jury for the shooting of Trayvon Martin and the decisions of several grand juries not to indict police officers for the killing of unarmed black men. Meanwhile, the overall use of juries has also declined in recent years, with most cases settled or resolved by plea bargain. With this text, the author offers a full-throated defense of juries as a democratic institution.
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 12, 2020).
Keywords: Jury -- United States; Jury duty -- Political aspects -- United States; Jury nullification -- United States; Law; Laws of specific jurisdictions & specific areas of law